Bragg spectroscopy for measuring Casimir-Polder interactions with Bose-Einstein condensates above corrugated surfaces - Moreno, Gustavo Ariel (2010)
We propose a method to probe dispersive atom-surface interactions by measuring via two-photon Bragg spectroscopy the dynamic structure factor of a Bose-Einstein condensate above corrugated surfaces. This method takes advantage of the condensate coherence to reveal the spatial Fourier components of the lateral Casimir-Polder interaction energy.